Flight Simulator Program in Secondary Surveillance for Air Defense Training - Khamlae, Ponlawat; Choensawat, Worawat; Sookhanaphibarn, Kingkarn (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2023)
This article presents a program for simulating aircraft in radar airspace for air defense training. The program is specifically designed for close-range and medium-range radar systems, which are crucial in training personnel to detect radar signals without the need for actual aircraft flights. The simulation program can replicate various scenarios, including training exercises with multiple radar systems and realistic situations with a dense number of aircraft. The article introduces an innovation that utilizes the simulation program, generating synthetic radar data from real data collected by FlightRadar24. The program features include: 1) simulating real data collected from FlightRadar24, 2) simulating data with noise synthesis techniques applied to actual data, and 3) generating diverse data using individual flight synthesis and air traffic density synthesis techniques. Experimental results demonstrate that the simulation program can be effectively utilized in real air defense systems.